Optimizing Learning Communities through a Systematic Literature Review: A Conceptual MOKBA Model for Enhancing Teachers’ Pedagogical Competence - Sinta Asih; Suryadi Suryadi; Deni Kadarsah; Nurdin Nurdin; Juliani Musti Khofifah (Research, Training and Philanthropy Institution Natural Aceh, 2026)
This study examines how Learning Communities support teachers’ pedagogical competence and proposes the MOKBA (Model for Optimizing Adaptive Learning Communities) as a managerial framework for sustainable professional learning. Using a qualitative systematic literature review guided by PRISMA, 18 articles published from 2020 to 2025 were selected from Google Scholar, DOAJ, and ERIC and analyzed through Miles and Huberman’s interactive model. The synthesis shows that Learning Communities strengthen four core dimensions of pedagogical competence: instructional design, classroom implementation, ICT integration, and assessment literacy. The most effective mechanisms are lesson study, peer coaching, collaborative design, and data-driven reflection. Based on these findings, MOKBA is formulated through four cyclical phases: needs diagnosis, collaborative design, guided implementation, and collective reflection with impact evaluation. The model positions Learning Communities not merely as informal collaboration spaces, but as accountable systems embedded in school quality management. This study contributes a conceptual framework for strengthening teacher professionalism, instructional quality, and sustainable school-based professional development.